The Hepatoprotective Role of Ethanolic Mangosteen Peel Extract (Garcinia mangostana L.) on MDA, TNF-α, E-Selectin, and SGPT Levels in Isoniazid-Induced Liver Fibrosis Wistar Rats - Triyanta Yuli Pramana; Rodi Nur Fajri; Brian Wasita; Eti Poncorini Pamungkasari (Gema Lingkungan Kesehatan, 2026)
Isoniazid is a first-line anti-tuberculosis drug known to cause drug-induced liver injury (DILI) through oxidative stress and inflammatory mechanisms that contribute to the development of liver fibrosis. Mangosteen peel (Garcinia mangostana L.) contains xanthone compounds with antioxidant and anti-inflammatory properties, making it a potential hepatoprotective agent. This study aimed to determine the role of ethanol extract of mangosteen peel on malondialdehyde (MDA) levels, tumor necrosis factor-α (TNF-α) expression, E-selectin expression, and SGPT levels in the liver of isoniazid-induced fibrosis Wistar rats. This experimental study used a post-test only control group design. Twenty-eight male Wistar rats were randomly divided into four groups: negative control group, positive control group (isoniazid 50 mg/kgBW/day), treatment group 1 (isoniazid + mangosteen peel ethanol extract 250 mg/kgBW/day), and treatment group 2 (isoniazid + mangosteen peel ethanol extract 500 mg/kgBW/day) for 30 days. MDA and SGPT levels were measured using spectrophotometry, while TNF-α and E-selectin expression were assessed using immunohistochemistry. Administration of mangosteen peel ethanol extract significantly reduced MDA and SGPT levels and decreased TNF-α and E-selectin expression compared to the positive control group. The most significant reduction was observed in the group receiving the extract dose of 500 mg/kgBW. Mangosteen peel ethanol extract reduces MDA, TNF-α, E-selectin, and SGPT levels in isoniazid-induced Wistar rats. These findings demonstrate its hepatoprotective potential in a preclinical setting, further translational and clinical studies are warranted to evaluate its efficacy and safety in humans as potential hepatoprotective agent.